1999
DOI: 10.1258/0956462991913286
|View full text |Cite
|
Sign up to set email alerts
|

An Outreach Programme for Sexually Transmitted Infection Screening in Street Sex Workers using Self-Administered Samples

Abstract: Street sex workers represent an at-risk group of individuals who find it difficult to access mainstream health services. This was a cross-sectional study of street sex workers in Melbourne, Australia using a self-administered method to detect chlamydial, gonorrhoea and trichomonas infections. Of the 81 individuals approached, 63 (78%) (95% CI: 67-86%) agreed to participate. Overall, 87% of the participants obtained their results. Of the 63 participants, 53 (84%) had a past history of injecting drug use (95% CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 4 publications
2
26
0
Order By: Relevance
“…Using a positive PCR test on endocervical swab specimens exclusively or in combination with positive results from at least two specimens to identify infected patients, or using the latent class model that does not assume any gold standard (29), the relative sensitivity and specificity of PCR on sanitary napkin specimens were 92 to 100% and 98 to 99%, respectively. These values are similar to those reported with vaginal swab specimens obtained by health care providers (22,26,31,33) and are similar to or slightly higher than those reported with self-collected vaginal swab specimens (2,5,9,15,16,31) or vaginal tampon specimens (13,(23)(24)(25).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Using a positive PCR test on endocervical swab specimens exclusively or in combination with positive results from at least two specimens to identify infected patients, or using the latent class model that does not assume any gold standard (29), the relative sensitivity and specificity of PCR on sanitary napkin specimens were 92 to 100% and 98 to 99%, respectively. These values are similar to those reported with vaginal swab specimens obtained by health care providers (22,26,31,33) and are similar to or slightly higher than those reported with self-collected vaginal swab specimens (2,5,9,15,16,31) or vaginal tampon specimens (13,(23)(24)(25).…”
Section: Discussionsupporting
confidence: 87%
“…More recently, detection of chlamydial infection by these techniques has also been assessed on secretions recovered from vaginal introitus collected by clinicians or patients themselves (2,5,9,15,16,22,26,31,33) or from vaginal tampons (13,(23)(24)(25). Urine and self-collected samples represent easy and noninvasive techniques compared to the usual cervical swabbing, which necessitates vaginal speculum insertion and a gynecologic examination.…”
mentioning
confidence: 99%
“…Probably several times as many work in this very transient sector of the sex industry during any one year. Notably a comparable number of sex workers solicit on the streets of Melbourne (Morton 1999) where street sex work is illegal and the potential client base is smaller. This suggests that the law has little effect on the presence of street prostitution.…”
Section: Discussionmentioning
confidence: 99%
“…In the north of Australia, the authors have found that a study carried out on aboriginal women has found an increase in the prevalence of the infection in T. vaginalis with age. 12,13 According to other authors, unlike Chlamydia trachomatis and N. gonorrhoeae, the young age is not a risk factor of trichomoniasis. The prevalence of T. vaginalis appears to increase with age for both sexes, perhaps due to the nature frequent asymptomatic infection and consequently the persistence of untreated infections.…”
Section: Discussionmentioning
confidence: 99%